2017
DOI: 10.1016/j.hrthm.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renal sympathetic denervation on the stellate ganglion and brain stem in dogs

Abstract: Background Renal sympathetic denervation (RD) is a promising method of neuromodulation for the management of cardiac arrhythmia. Objective We tested the hypothesis that RD is antiarrhythmic in ambulatory dogs because it reduces the stellate ganglion nerve activity (SGNA) by remodeling the stellate ganglion (SG) and brain stem. Methods We implanted a radiotransmitter to record SGNA and electrocardiogram in 9 ambulatory dogs for 2 weeks, followed by a 2nd surgery for RD and 2 months SGNA recording. Cell deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…Besides the antihypertensive effects of RDN, an experimental study by Tsai and colleagues showed the antiarrhythmic effects of RDN in six ambulatory dogs by measuring lower nerve activity at the level of the stellate ganglion with also a decrease in paroxysmal atrial tachycardia episodes and duration after RDN as compared to controls [ 10 ]. Moreover, two clinical studies assessed the antiarrhythmic effect of RDN in addition to PVI in hypertensive patients with symptomatic AF.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the antihypertensive effects of RDN, an experimental study by Tsai and colleagues showed the antiarrhythmic effects of RDN in six ambulatory dogs by measuring lower nerve activity at the level of the stellate ganglion with also a decrease in paroxysmal atrial tachycardia episodes and duration after RDN as compared to controls [ 10 ]. Moreover, two clinical studies assessed the antiarrhythmic effect of RDN in addition to PVI in hypertensive patients with symptomatic AF.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that several different routes (i.e. carotid sinus) contribute with collapse between synapses (Tsai et al, 2017), as afferent renal nerve ganglionic cells situated in lumbar and thoracic dorsal root ganglia of the spinal cord also connect to hypothalamic nucleispecifically the posterior and lateral areas, and the locus ceruleus (Campese and Kogosov, 1995;Jansen et al, 1995). Together these data suggest that long-term RDN results may possibly occur due to remodeling of crucial brainstem sites and both SG.…”
Section: Renal Denervationmentioning
confidence: 90%
“…Renal denervation may blunt sympathetic overactivity and arrhythmogenic foci, thereby potentially reducing arrhythmogenic activity. Preclinical data have shown remodeling of the stellate ganglion (SG) and the brain stem ∼2 months post-RDN, likely medaited by afferent renal nerve signaling interruption (Tsai et al, 2017). Also, a reduction of 18 FDGuptake, SG sympathetic traffic and atrial tachyarrhythmias were correlated to neural modifications of these structures.…”
Section: Renal Denervationmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have shown that bilateral RDN led to substantial neuronal remodeling in the brain stem and stellate ganglia following the RDN procedure. [34][35][36][37] The renal efferent sympathetic nerves arising from the second sympathetic ganglion form a network within the renal artery adventitia 38 that is regulated by the rostral ventrolateral medulla, the destruction of which substantially reduces BP. 39 Accordingly, the RDN procedure was introduced to disrupt the sympathetic crosstalk from the kidneys to the brain and vice versa as well as between the two kidneys.…”
Section: Mechanisms Of Rdn-induced Clinical Benefitsmentioning
confidence: 99%